How do young people respond to conflict? A comparative study of Argentinean and Portuguese college students - Silva, Ana Maria Costa e (2021)
Questions relating to sociability, relationships concerning conflicts and behaviours of indiscipline and violence among young people have turned out to be of particular importance. Various studies exist about the sociability of young people (e.g. Machado Pais, 1990; Margulis - Urresti, 1998; Cangilini, 2004). Nevertheless, studies focused on sociability and behavior in the face of socially learned conflicts in the context of inter-personal relationships are still very scarce. The investigation carried out falls within the area of Co-operative Conflict Resolution (CCR) - a field of knowledge and practices that emerged in the 1980s (Ury - Fisher, 1991; Aréchaga, Brandoni - Finkelstein, 2004). The work that we present shows the results of a study undertaken with young people attending the first year of university education in public and private universities in Argentina and Portugal. This investigation, which was of an exploratory nature, had two general objectives: i) to analyse the ways of approaching conflicts by young people (aged 18 to 31 years); and ii) to understand the present day social dynamics that characterise these young people. The descriptive analysis of the data, which was obtained from the responses to a questionnaire with open and closed questions completed by around 700 young university students, revealed some differences concerning the behaviour adopted towards conflicts by these young Argentineans and young Portuguese. ; Sociability; Relationships; Conflicts; Young people; Co-operative Conflicts Resolution